2018
DOI: 10.1016/j.accpm.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an electronic checklist in the ICU: Association with improved outcomes

Abstract: In this matched before/after study, implementation of an electronic checklist was associated with positive effects on patient outcomes, especially on VAP. Further prospective studies are needed to confirm these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This issue could be overcome by tools that facilitate compliance without delaying the management of patients. For example, the implementation of an electronic checklist was associated with a reduction in the incidence of healthcare-associated, ventilator-associated pneumonia by improving the application of preventive measures [18]. Such an approach in the context of trauma has been proposed by Sarcevic et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…This issue could be overcome by tools that facilitate compliance without delaying the management of patients. For example, the implementation of an electronic checklist was associated with a reduction in the incidence of healthcare-associated, ventilator-associated pneumonia by improving the application of preventive measures [18]. Such an approach in the context of trauma has been proposed by Sarcevic et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rates range from 15 to 25%, and 21% of patients discharged alive does not survive at 1-year [6]. A longitudinal study highlighted a trend toward increasing proportions of elderly patients between 2008 and 2014 [7].…”
Section: Admission Criteria and Outcomementioning
confidence: 99%
“…Numerous studies have demonstrated the significance of appropriate physician staffing as well as the use of protocols, clinical practice guidelines, and checklists to improve clinical outcomes in modern ICUs [3][4][5]. Specifically, some studies have shown that Healthcare 2024, 12, 871 2 of 14 the implementation of checklists for organized critical care in ICUs improved patients' outcomes [6,7].…”
Section: Introductionmentioning
confidence: 99%